Compendium of industry profiles (Caribbean Technology Consultancy Services St MichaelBB, 1986)
Contains six industry profiles relating to coir fibre extraction, rubber door mats made from old car tyres, paint brushes manufacturing, dry cleaning operation, production of safety matches and a cement bagging plant, which have been planned/established in the English speaking Caribbean. Also contains 12 profiles drawn from the publication `How to Start Manufacturing Industries', published by UNIDO. Each profile describes the raw materials and equipment needed and gives approximate costs. In some cases describes production process and gives indications of manpower requirements. Provides technical characterisitcs of the manufacturing plant.
IDS